2018
DOI: 10.1105/tpc.17.00771
|View full text |Cite
|
Sign up to set email alerts
|

Far-Red Light Detection in the Shoot Regulates Lateral Root Development through the HY5 Transcription Factor

Abstract: Plants in dense vegetation compete for resources and detect competitors through reflection of far-red (FR) light from surrounding plants. This reflection causes a reduced red (R):FR ratio, which is sensed through phytochromes. Low R:FR induces shade avoidance responses of the shoot and also changes the root system architecture, although this has received little attention so far. Here, we investigate the molecular mechanisms through which light detection in the shoot regulates root development in We do so using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
196
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(210 citation statements)
references
References 95 publications
(129 reference statements)
12
196
1
1
Order By: Relevance
“…Intra-or interspecies plant mutual shading often affects crop light interception [2], especially in intercropping and close planting system which are important cultivation methods in increasing resource utilization and yield [3]. Plants can perceive shading that enable them to acclimate and adjust their phenotypic and physiological characteristics to compete for limited light resource [4]. Shade often leads to elongation responses in the stem, petioles, and leaves in shadesensitive plant species [5].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-or interspecies plant mutual shading often affects crop light interception [2], especially in intercropping and close planting system which are important cultivation methods in increasing resource utilization and yield [3]. Plants can perceive shading that enable them to acclimate and adjust their phenotypic and physiological characteristics to compete for limited light resource [4]. Shade often leads to elongation responses in the stem, petioles, and leaves in shadesensitive plant species [5].…”
Section: Introductionmentioning
confidence: 99%
“…ELONGATED HYPOCOTYL 5 ( HY5 ) acts as a mobile signal mediating root-to-shoot communication in response to light quantity and quality [22–24]. hy5 mutants exhibit root systems with reduced primary root length, however, lateral root development is accelerated, relative to WT [23].…”
Section: Resultsmentioning
confidence: 99%
“…As for the first mechanism, it has been suggested that HY5, one of the best characterized targets of COP1-mediated degradation, might directly regulate PIN1 transcription in the hypocotyl [96]. Notably, recent work has shown that HY5 is a shoot-to-root mobile signal that mediates light promotion of root growth [97,98]. Perception of Low R/FR in the shoot also results in a decrease in lateral root (LR) emergence, and it has been proposed that HY5 regulates this process by inhibiting the auxin efflux carrier PIN3 and the influx carrier LIKE-AUX1 3 (LAX3) auxin transporters, which act in concert in the process of LR emergence [98,99].…”
Section: Auxin Transportmentioning
confidence: 99%